SARS-COV-2 en pacientes con Tuberculosis. - Montesdeoca Berrones, Bethy Margarita (2023)
ABSTRACT: The present literature review aimed to describe the nursing interventions to be applied in patients with COVID-19 and tuberculosis. The COVID-19 pandemic has generated additional pressure on health systems, and coexistence with tuberculosis presents additional challenges due to the need for stricter infection control measures and greater complexity in clinical management. Nursing care in patients with COVID-19 and tuberculosis co-infection is a challenge that requires specialized and comprehensive care. The intersection of these two respiratory diseases presents unique complexities that must be addressed comprehensively, nursing professionals play a vital role from early identification of symptoms to implementation of infection prevention and control measures. In addition, they must tailor their approaches to care to address the specific needs of patients with coinfection, considering the complexity of therapies, potential side effects of medications, and the emotional burden patients face.